Perspektif Islam Tentang Keikutsertaan Perempuan Dalam Politik Dinasti - Muhammad Muhaimin (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2025)
Nowadays, there has been an escalation of transformation that rejects barbaric acts against women or gender bias, even in several countries women have been found holding crucial positions such as leading the government, politicians, officials and so on. The normative method is used in this study, namely based on Islamic law in the form of the hadith of the Prophet Muhammad SAW as primary data, while library materials from books and journals act as secondary data. The research method is used to answer the question of how Islam views women's participation in dynasty politics. The results of this study indicate that the presence of dynasties in the past that involved women can be a basis for their permissibility in the present, as long as the leadership meets the provisions of applicable Islamic law. The main concept of Islamic understanding of the realization of dynasty politics is related to the leadership aspect, namely that it must be in accordance with qualifications and pay attention to sharia and social justice.